Approximate Controllability for Fuzzy Fractional Evolution Equations of Order ℓ ∈ (1, 2) - Hariharan, R; Udhayakumar, R (Contemporary Mathematics, 2024)
This study focuses on exploring the concept of approximate controllability in nonlocal Cauchy problems associated with fuzzy fractional evolution equations of order ℓ ∈ (1, 2). Our approach combines fuzzy theory, fractional calculus, and Krasnoselskii’s fixed point theorem to establish key findings. Our primary objective is to establish the approximate controllability of these fuzzy fractional systems. Additionally, we provide a theoretical example to illustrate the implications of our findings.